Prinsip Larangan Dalam Perbankan Syariah Sebagai Instrumen Penjaga Kepatuhan Syariah - Satrya Ramadhan Anggara; Robitoh Rizqiana Dinova; Ananda Viola Maharani; Nasywa Anindita Alvania Putri Irawan; Baidhowi (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the prohibition principle in Islamic banking as an instrument for maintaining Sharia compliance, as well as to identify Sharia compliance challenges and formulate preventive measures to uphold the prohibition principle in Islamic banking. This study uses a literature review method by examining scientific journals, laws and regulations in the field of Islamic banking, and fatwas issued by the Indonesian Ulema Council's National Sharia Board. The data obtained is analyzed qualitatively to understand the application of the prohibition principle as an instrument for maintaining sharia compliance in Islamic banking. The discussion shows that the prohibition principle in Islamic banking functions as the main instrument in maintaining sharia compliance and preserving substantive differentiation from conventional banking. This principle is not only normative but also operational because it has direct implications for the design of contracts, governance, and risk management in Islamic banking. Sharia compliance is proven to be highly determined by the effectiveness of the Sharia Supervisory Board in overseeing the conformity of bank products and activities with the fatwa of the Indonesian Ulema Council's National Sharia Board. However, in practice, there are still challenges in the form of substantive contract deviations, limited supervisory capacity, the impact of digitalization, and low public literacy, which have the potential to cause sharia non-compliance risks. Therefore, strengthening sharia governance, standardizing contracts, improving the competence of the DPS, and integrating technology that supports supervision are important steps to maintain the sustainability of Islamic banking within the framework of supervision by the Financial Services Authority.